"We can stop work, but then nothing gets done." Factors that support and hinder a workforce to discontinue work for safety. (October 2018) - Weber, David E.; MacGregor, Sean C.; Provan, David J.; Rae, Andrew
Highlights: Stopping work for safety is challenging at times. Stopping does not solely hinge on the willingness of individual workers to stop. Stopping is dependent on contextual factors that influence the stop work decision. Contextual factors involve procedural, social, technical, and non-technical aspects. An Authority to Stop has to be embedded in and supported by a stop work environment. Abstract: Workers have a legal obligation not to perform unsafe work. In many organisations this obligation is supported by an explicit authority to discontinue work or to stop the work of others if the conditions of work are unsafe. The supporting document is often called an 'Authority to Stop an Unsafe Task.' However, when conducting work at the sharp operational end of the organisation, stopping work for safety might be challenging at times. A better understanding is required about the stopping of work and the application of an 'Authority to Stop.' The aim of this research is to identify some of the factors that support and hinder a workforce to effectively stop work when a task is deemed unsafe. 10 focus groups were conducted with workers of various roles in the liquefied petroleum gas (LPG) industry. The findings outline reasons to stop, challenges and supporting factors of stopping, as well as ways of stopping. The results indicate that the stopping of an unsafe task does not solely hinge on the willingness of individual workers to stop, but also depends on contextual factors surrounding the stop work decision.